The Effectiveness of Phonetic Transcription in EFL Students Pronunciation - Cansa Namira Sitanggang; Hafizah Ismayati; Bima Bahari; Yani Lubis (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2023)
This journal aims to analyze the effectiveness of using phonetic symbols in the pronunciation of students who speak English as a foreign language (EFL) by measuring students' capabilities in pronouncing English reading or sentences with phonetic transcription. This study explores to what extent the use of phonetic symbols can help EFL students improve their pronunciation. The research method used Quantitative Descriptive by using table percentage with 25 EFL students in 4th semester in the English department from State Islamic University of North Sumatera as participants. These students were selected to read the sentences with phonetic transcription by using WhatsApp application and Voice note features to read the sentences. During the research, students weren't given teaching materials containing phonetic symbols and were asked to read and pronounce the English sentences with their pure ability. Data was collected through pronunciation tests. This test is intended to measure students' pronunciation abilities and the progress in reading sentences using phonetic symbols. The results showed that there were 72% of the English department students who were categorized as capable in reading sentences using phonetic transcription and 28% of all students are incapable of reading the sentences provided. It was concluded that the phonetic symbols helped EFL students to pronounce difficult sounds in English. In conclusion, the use of phonetic symbols proved effective in improving the pronunciation of EFL students. Phonetic symbols can be a useful tool in helping students improve their pronunciation in speaking English due to the capability of most students in reading English sentences.